Busk Forestry Enterprise (Ukraine): Historical and Geographical Formation Features and Current State - Bohdan Havryshok; Miroslav Syvyi; Petro Demyanchuk; Victoria Hrytsyshyn; Myroslava Pytuliak (Research Advances in Environment, Geography and Earth Science Vol. 8, 2024)
Our research is based on the processing and territorial interpretation of statistical data from the Busk Forestry Enterprise. Based on these data, we constructed and analyzed maps showing species composition, age structure, and wood stock across different forestry districts. The following characteristic features of the region’s forestry were identified: uneven forest cover in the studied area, significant fragmentation of the forest fund in the southern part of the forestry’s activity zone, the location of large forested areas in the northwestern part of the forestry, dominance of species such as pine, oak, and alder, slight increase in forest cover in certain areas due to the creation of pine plantations on non-agricultural lands, and the active expansion of black alder forests on waterlogged pastures. The aim of the proposed study is to conduct a geospatial examination of the species composition, age structure, and economic use of the Busk Forestry Enterprise’s forest plantations, as well as a retrospective geographical assessment of the forestry territory formation. The practical importance of the research increases in the context of land resource management in newly created communities. The spatial aspects we have developed will also be useful for forestry workers both in the process of consolidating forestry enterprises and in the formation of new forest plantations. The research was conducted using cartographic materials from different periods, allowing us to trace the development of typical forested areas from the late 18th century to the present. We employed the method of temporal cross-sections and a diachronic approach. The study includes fragments of cartographic materials for key areas. We examined the division of the forest fund by categories and established that the largest portion of the Busk Forestry Enterprise’s forest fund is occupied by operational forests. Protective forests account for 1.5% of the total forest area in the studied region. Forest availability for the population in the Krasnensky territorial community averages 0.12 hectares per person, while in the Busk community, it is 0.61 hectares per person.